API Management Platforms - Lehtonen, Aleksi (My University, 2023)
Goals of the thesis are to introduce reader to APIs and API management and core concepts within those. These concepts help reader to understand the benefits of having an API management platform to control APIs in an organization, and how it links to integration strategy and architecture. Scope of the thesis is to stay within things related to API management platforms. As API management platforms are a product that heavily links into ways of doing integrations, integration strategy and architecture had to be included in the thesis as concepts, but they are not looked too deeply into. Research methodologies in the thesis consists of interviews of experts, review of scientific literature, and comparisons done between products. Thesis provided results that showed the importance of integration strategy when choosing a big tool such as API management platform. API management platform plays a big part in the integration architecture of a company, which is directly linked to integration strategy. This thesis could be used in an organization to help build guidelines for integration strategy, while considering API management as one of the main concepts. Another use for the thesis could be to use it as a roadmap to choose the right API management platform for an organization.
Keywords: API Management platforms, Integration strategy, Integration architecture